Analisis daya tampung beban pencemaran sungai bedadung Jember menggunakan software wasp - Novita, Elida; Bisri, Moch. Imron Mustofa; Pradana, Hendra Andiananta (Universitas Gadjah Mada, 2023)
The distribution of pollution sources from domestic, agricultural, and industrial activities has the potential to reduce the water quality of the Bedadung River, thereby negatively impacting its self-purification. The aim of this research is to model the parameters, specifically the values of Biochemical Oxygen Demand (BOD) and Total Suspended Solid (TSS), and to determine the river's capacity to carry the pollution load using the Water Quality Analysis Simulation Program (WASP). The input parameters for this study include BOD, TSS, and water discharge data collected at 21 monitoring points along the Bedadung River, with the river water sampling technique employing the grab sampling method. The output validation of the modeling is assessed using the Root Mean Square Error (RSME) equation, and the research results indicate that the water quality modeling with WASP software effectively reflects the dynamics of BOD and TSS parameters in the Bedadung River, as supported by an average output validation value of 9%. The pollution load capacity values for the Bedadung River in the Patrang - Ajung segment are found to be 361.48 kg/day for BOD and 5368.31 kg/day for TSS. The positive values suggest that the Bedadung River still has the capacity to naturally degrade organic pollutants.